De novo analysis reveals transcriptomic responses to heat stress in loquat leaves. (16th November 2021) - Ma, Shiwei; Lin, Shoukai; Wu, Bisha; Lin, Hailan; Lin, Dahe; Chen, Yu; Lin, Suying; Lin, Shunquan; Wu, Jincheng
Abstract: Temperature has a vital impact on plant growth and development, and heat stress severely threatens agricultural productivity and food security. High temperatures can cause annual yield reductions and disease in loquat [ Eriobotrya japonica (Thunb.) Lindl.]. However, the molecular mechanisms underlying the heat stress response in loquat are not known. In this study, the transcriptome of loquat leaves in response to heat stress was sequenced and assembled de novo, and differentially expressed genes (DEGs) were identified. A total of 16, 120 and 11, 668 DEGs were identified at 1 and 2 h posttreatment, respectively. Gene ontology (GO) analysis indicated that the DEGs were located in the membrane and endoplasmic reticulum and were related to signal transduction and protein modification. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that the heat‐induced DEGs were mainly related to the activation of protein processing in the endoplasmic reticulum and transcription. Ninety‐six heat shock proteins ( HSPs ) were also found in the protein processing pathway in the endoplasmic reticulum, and most HSPs were induced by heat stress. Heat shock transcription factors regulating the expression of downstream HSPs were induced by heat together with HSPs . This research provides insights into the mechanism of loquat plant heat stress tolerance and paves the way for heat‐tolerant loquat breeding. Core Ideas: The transcriptome of loquat leaves suffering heat stress were sequenced and de novo assembled. Differentially expressed genes response to heat stress was enriched in protein processing in endoplasmic reticulum. The upregulated heat shock proteins (HSPs) in the pathway were the dominant component of the heat stress response. Heat shock transcription factors regulating the expression of HSPs were induced by heat together with HSPs.